Remember the Future: Prehistoric Design and Sustainability - Bofylatos, Spyros; Balaskas, Taxiarxis (FormAkademisk, 2023)
The starting point of this study is the prehistoric “teganoschemo” archaeological find of the Syros-Keros civilization in the Aegean Sea. These artifacts have been causing debates among archaeologists as their raison d'être is still contested. The aim of this study is to bring a prehistoric ontological model of design and craft to contemporary design practices. In order to explore such alternative ontologies, we turn to the past and address themes of death and life embodied in these prehistoric artifacts. As we leave Modernity behind and transition towards Sustainment, a new ontology for Design is necessary. By understanding the ontological framework of prehistoric designers, we aim to create propositional artifacts that exemplify what design can be. The propositional artifacts created act as different phases in a research-through design process that aims to investigate how design operates within an alternative system of values.